A height‐reduction antenna with simple structure for base station. Issue 8 (21st May 2022) - Jiang, Jin; Chu, Qing‐Xin; Chang, Yu‐Lin
Abstract: In this article, a height‐reduction dual‐polarized antenna suitable for base station applications with a simple structure is proposed. By adopting the form of bilateral coupling feed, the height of the antenna has been significantly reduced. The working mechanism of height‐reduction of the antenna is given. The experimental results show that the antenna operates at 0.698–0.96 GHz for reflection coefficient <−12 dB with isolation (ISO) of more than 30 dB. It has a stable gain of 8.4 ± 0.6 dBi and a half‐power beamwidth (HPBW) of 66.8 ± 6.8° in the working band, and the height of the proposed antenna is only 0.115 λ 0, which is much smaller than the traditional 0.25 λ 0 ( λ 0 denotes the free wavelength corresponding to the center frequency).